Evaluación de nutrición edáfica en cultivo de nabo (brassica rapa subsp) en la granja experimental santa inés - Illescas Moreno, Giannella Carolina (Machala : Universidad Técnica de Machala, 2021)
Turnip (Brassica rapa Subsp) is a vegetable that does well in any type of climate, but is particularly adapted to cold climates. It belongs to the Brassicaceae family of which there are 380 genera and 3000 species. In Ecuador the Sierra region has 86% of participation in growing vegetables, then the Coast region and finally the East. The main provinces that are within the highlands that are producers of vegetables: Tungurahua, Chimborazo, Azuay, Pichincha and Cotopaxi in which the canton Saquisili has the largest production for 40 years, where they grow turnip and sell to different markets in some cities of Ecuador. In the province of El Oro, Machala, Guabo, Pasaje and Chilla have exotic flora and fauna and grow vegetables such as lettuce, turnip, broccoli and tropical fruits for consumption of the basic baskets of the orenses. These provinces have climates and soils that favor the cultivation of vegetables, which is very required for the diet. With the objective of using fertilization in combination of Urea, Ammonium Nitrate, Biocompost and Biochar in turnip crop to evaluate the foliar development of the crop and to know the effect of biochar in relation to root growth. The present research was carried out at the Technical University of Machala Granja Santa Inés, using a completely randomized design (CRD) with seven treatments and one control, each with 15 replications: T1: Ammonium Nitrate (2g); T2: Urea (2g); T3: Biochar (1g) + Ammonium Nitrate (1g); T4: Biochar (1g) + Urea (1g); T5: Biochar (1g) + Ammonium Nitrate (1g) + Biocompost (1g); T6: Charcoal + Urea + Biocompost (1g); T7: Biochar (2g) and the Control. The variables evaluated were: total leaves (HT), leaf length (LH), leaf width (AH), root weight (PR), root length (LR), root width (AR), fresh matter weight (PMF), dry matter weight (PMS). Data were analyzed with SPSS statistical software using one-factor ANOVA and Duncan's test (∝= 0.05). According to the results if there is significant difference in the variables LH, PR, LR, AR, PMF, PMS and there is no significant difference in the variables HT, AH, the results obtained indicate that the best treatment to obtain a good yield in turnip crop was the T4 treatment (biochar + urea) with an average of 786.55 g of fresh matter production due to the combination between nitrogen fertilization biochar. In T2 (Urea) with 50.16 cm is the highest value in the leaf length variable, and for the root width variable (21.85 mm), in this treatment strong and vigorous roots were evidenced. Urea as a source of foliar nitrogen is considered very appropriate because it has advantages for its rapid absorption, translocation and assimilation by the plant. As a recommendation, use urea with biochar to obtain a good turnip crop, with well-developed leaves to increase the yield of this crop.
El nabo (Brassica rapa Subsp) es una hortaliza que se condiciona bien en cualquier tipo de clima, pero particularmente se adapta a climas fríos. Pertenece a la familia brassicaceae de los cuales son 380 géneros y 3000 especies. En el Ecuador la región Sierra tiene el 86% de participación en cultivar hortalizas, luego la región Costa y finalmente el Oriente. Las principales provincias que están dentro de la sierra que son productoras de hortalizas: Tungurahua, Chimborazo, Azuay, Pichincha y Cotopaxi en el cual el cantón Saquisili tiene mayor producción desde hace 40 años, donde cultivan el nabo y comercializa a distintos mercados en algunas ciudades del Ecuador. En la provincia de El Oro se encuentra Machala, Guabo, Pasaje y Chilla donde tiene flora y fauna exótica, se cultiva hortalizas como lechuga, nabo, brócoli y también frutas tropicales, para el consumo de las canastas básicas de las orenses. Estas provincias tienen climas y suelos que favorecen al cultivo de las hortalizas, que es muy requerida para la dieta alimenticia. Con el objetivo de usar fertilización en combinación de Urea, Nitrato de Amonio, Biocompost y Biocarbón en cultivo de nabo para evaluar el desarrollo foliar del cultivo y conocer el efecto del biocarbón en relación del crecimiento de la raíz. La presente investigación se realizó en la Universidad Técnica de Machala Granja Santa Inés, se empleó un diseño completamente al azar (DCA) con siete tratamientos y un testigo cada uno con 15 repeticiones: T1: Nitrato de Amonio (2g); T2: Urea (2g); T3: Biocarbón (1g) + Nitrato De Amonio (1g); T4: Biocarbón (1g) + Urea (1g); T5: Biocarbón (1g) + Nitrato De Amonio (1g) + Biocompost (1g); T6: Carbón + Urea + Biocompost (1g); T7: Biocarbón (2g) y el Testigo. las variables evaluadas fueron: hojas totales (HT), largo de hoja (LH), ancho de hoja (AH), peso de raíz (PR), largo de raíz (LR), ancho de raíz (AR), peso de materia fresca (PMF), peso de materia seca (PMS). Los datos se analizaron con el software estadístico SPSS mediante el ANOVA de un factor y la prueba de Duncan (∝= 0.05). Según los resultados si existe diferencia significativa en las variables LH, PR, LR, AR, PMF, PMS y no existe diferencia significativa en las variables HT, AH, los resultados obtenidos señalan que el mejor tratamiento para obtener un buen rendimiento en el cultivo de nabo fue el tratamiento T4 (biocarbón + urea) con una media de 786,55 g de producción de materia fresca debido a la combinación entre la fertilización nitrogenada biocarbón. En el T2 (Urea) con 50,16 cm es el valor más alto en la variable longitud de hoja, y para la variable ancho de raíz con (21.85 mm), en este tratamiento se evidenciaron raíces fuertes y vigorosas. la urea como fuente de nitrógeno foliar es considerada muy apropiada porque tiene ventajas para su rápida absorción, translocación y asimilación por la planta. Como recomendación utilizar la urea con el biocarbón para obtener un buen cultivo de nabo, con hojas bien desarrolladas aumentar el rendimiento en este cultivo.
Keywords: FERTILIZACIÓN; RENDIMIENTO; EFECTO; CARBÓN